A Parallel-Strip Balun for Wideband Frequency Doubler. (4th December 2013) - Chiu, Leung; Xue, Quan
Abstract : A parallel-strip phase inverter with a pair of simple impedance matching networks is designed. The phase inverter introduces the almost frequency independent 180° phase shift and was employed in the wideband parallel-strip balun. The balun was designed and measured with the maximum magnitude imbalance of 0.5 dB and the maximum phase imbalance of 6.0°. The proposed balun is used as input network for the wideband balanced frequency doubler. The proposed frequency doubler achieves significant conversion gain from 0.1 GHz to 1.7 GHz. The frequency doubler achieves 7.4 dB conversion gain and 23 dB fundamental signal suppression at 1 GHz.